English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Can anyone work out these 3 analogies and tell me how to do them? I have been trying for ages!

9 is to 16 as 4 is to 6 as 3 is to ? the answer is either 4 5 7 8 10
5 is to 8 as 8 is to 14 as 3 is to ? the answer is either 2 4 6 7 9
3 is to 10 as 8 is to 25 as 6 is to ? the answer is either 13 19 22 23 24

please help!?

2006-07-20 02:37:19 · 12 answers · asked by wolf 2 in Science & Mathematics Mathematics

12 answers

right...
1) 4
2) 4
3) 19

For 1 and 2 you double the number and minus two, eg
1) 9 x 2 = 18 - 2 = 16
4 x 2 = 8 - 2 = 6

Therefore, 3 x 2 = 6 - 2 = 4

2) 5 x 2 = 10 - 2 = 8
8 x 2 = 16 - 2 = 14

Therefore, 3 x 2 = 6 - 2 = 4

And for number 3, you multiply by three and add one, eg
3) 3 x 3 = 9 + 1 = 10
8 x 3 = 24 + 1 = 25

Therefore, 6 x 3 = 18 + 1 = 19

2006-07-20 02:41:35 · answer #1 · answered by Anonymous · 5 2

Note the pattern in the sequence,

1, 2, 3, 4, 5, 6, 7, 8, 9, 10, ...

9 is to 16 (note 7 + 9 = 16)
4 is to 6 (note 2 + 4 = 16)
3 is to 4 (note 1 + 3 = 4)

5 is to 8 (note 3 + 5 = 8)
8 is to 14 (note 6 + 8 = 14)
3 is to 4 (note 1 + 3 = 4)

3 is to 10 (note 2 + 3 + 5 = 10)
8 is to 25 (note 7 + 8 + 10 = 25)
6 is to 19 (note 5 + 6 + 8 = 19)

2006-07-20 12:58:59 · answer #2 · answered by ideaquest 7 · 0 0

It would appear that you add the previous odd or even number as appropriate

ie 9 is to 16 - the previous odd number is 7 (9 + 7 = 16)
4 is to 6 - the previous even number is 2 (4 + 2 = 6)
therefore 3 is to 4 - the previous odd number is 1 (3 + 1 = 4)

the second one also seems to have the same rule.

the final one appears to be the number mulitplied by 3 +1

ie 3 x 3 =9 + 1 = 10
8 x 3 =24 + 1 = 25
6 x 3 =18 + 1 = 24

hope that makes sense !

2006-07-20 09:57:28 · answer #3 · answered by barneyboomagoo 4 · 0 0

9 + (9-2) = 16; 4 + (4-2) = 6; so 3 + (3-2) = 4
5 + (5-2) = 8; 8 + (8-2) = 14; so 3 + (3-2) = 4
3 * 3 + 1 = 10; 3 * 8 + 1 = 25; so 3 * 6 + 1 = 19

2006-07-20 09:43:33 · answer #4 · answered by Larry 6 · 0 0

em, ok
1st:9x2 = 18 - 2= 16
4x2 = 8 - 2= 6
so 3 x 2= 6 - 2 = 4

2nd:5x2=10 - 2=8
8x2=16 - 2=14
so 3x2=6 - 2= 4

3rd: well 3 x3 = 9 +1 = 10
8x3 = 24 +1 = 25
So 6 x 3 = 18 +1 = 19

Basically the first one and the second one are basically the same.

Hope this helps.

2006-07-20 09:45:26 · answer #5 · answered by Alistair B 3 · 0 0

Off the top of my head I would say the answer to the first one is 4.

2x9=18-2=16
2x4=8-2=6 so
2x3=6-2=4

2006-07-20 09:43:01 · answer #6 · answered by Michelle 4 · 0 0

Just divide and see what you have, 2x9=18 so it's 2 more than 16 2x4-8, 2 again, now the answer is easy.

2006-07-20 09:47:30 · answer #7 · answered by Anonymous · 0 0

the first two seem to be ' double the 1st number, then minus 2.
the second one 'multiply the 1st number by 3 then add 1

2006-07-20 09:43:09 · answer #8 · answered by fishfinger 4 · 0 0

4 - doubled and minus 2
4 - doubled and minus 2
19 - trebled and add 1

2006-07-20 09:44:18 · answer #9 · answered by jonnnboy 4 · 0 0

yep

4 doubled -2
4 doubled -2
19 x3 +1

2006-07-20 09:50:31 · answer #10 · answered by Richard S 1 · 0 0

fedest.com, questions and answers